A modified H-bridge multilevel inverter for photovoltaic system - Abd Rahim, N.; Chaniago, K.; Selvaraja, J. (IEICE-Inst Electronics Information Communications Eng, 2010)
This paper presents a modified H-bridge seven-level single-phase grid-connected inverter for photovoltaic system with a novel pulse-width-modulated (PWM) control scheme. The inverter is capable of producing seven output-voltage levels (V-dc, 2V(dc)/3, V-dc/3, 0, -V-dc, -2V(dc)/3, -V-dc/3) from the dc supply voltage. Perturb and Observe (P&O) algorithm is used to extract maximum power from the PV module. MPPT and current control algorithm were implemented in an eZdsp board, TMS320F2812. The proposed system was implemented in a prototype.